Visitors and the Exterior Image of the Museum of Fine Arts of Valladolid: 1842–1933 (BSAA arte, 2023)
The Provincial Museum of Fine Arts of Valladolid has a long history that its conversion into National Museum of Sculpture in 1933 has obscured. Through this study, we analyse its history up to this moment. We use various sources for this. First, there are the testimonies that some visitors left in their travel books, especially during the 19th century. In order to find out more about the people who visited the museum, we have also made use of the museum’s signature books for the period between 1915 and 1933. Reading the news published in the local newspaper El Norte de Castilla throughout this period, the available data are completed. All this allows us to know how the museum was like then, who came to visit it and in many instances the consideration it deserved.
Keywords: Museology; history of museums; visitors of museums; tourism